The Effects of Hepes Buffer on Clotting Tests, Assay of Factors V and VIII and on the Hydrolysis of Esters by Thrombin and Thrombokinase - Roberts, Phyllis S.; Hughes, Haywood N.; Fleming, Patricia B. (Thrombosis and Haemostasis, 1976)
Shorter clotting times were found in the presence of 50 mM Hepes (N-2-hydroxyethylpiper-azine-N1-2-ethanesulfonic acid) buffer than of 50 mM Imidazole buffer in one-stage assays of factors V and VIII, in modified APTT and PT tests and in tests of the clotting of human plasma by purified human thrombin. All tests were performed at ionic strength 0.155 in the presence of either Hepes. NaOH or Imidazole. HC1 buffer, pH 7.4 at 37°. The faster clotting in the presence of Hepes buffer, therefore, is probably due, at least in part, to acceleration by Hepes of thrombin’s enzymatic action on fibrinogen and/or of the polymerization of the fibrin monomers.Hepes may also have effects on other blood clotting reactions. Rates of hydrolysis of TAME or BAME (p-toluenesulfonyl-or benzoyl-L-arginine methyl ester) at pH 7.4, 37° by purified human or bovine thrombin were essentially the same in 200 mM Hepes as in 250 mM Tris. HQ buffer (rates in Hepes. NaOH or Hepes. KOH buffers were compared with those in Tris. HQ plus NaCl for KC1). However, with purified bovine thrombokinase, rates of TAME hydrolysis in Hepes buffer were accelerated and rates of BAME hydrolysis slightly inhibited. Hepes, therefore, reacts with thrombokinase but whether this accelerates (or inhibits) the rate of converting prothrombin to thrombin remains to be determined. In addition, Hepes has an inhibitory effect on clotting since increasing the concentration of Hepes from 50 mM to 200 mM inhibits clotting in the PT, APTT and bovine thrombin-human plasma tests.Hepes buffer is being added to some plasmas and to some reagents used in clotting tests. It is, therefore, important to realize that its concentration must be monitored closely or erroneous results may be obtained in clotting tests and assays of clotting factors.The clotting times were the same in the presence of 50 mM Tris. HC1 as in Imidazole. HC1 buffers in APTT tests at three ionic strengths but they differed slightly in plasma-thrombin tests. Depending upon the ionic strength, 17 mM Barbital Sodium. HC1 buffer inhibited APTT tests but accelerated plasma-thrombin tests. All the buffers tested, therefore, have individual effects on the clotting tests.